Responsive Thiolactone‐Derived N‐Substituted Poly(Urethane‐Amide)s. Issue 7 (13th February 2017) - Espeel, Pieter; Celasun, Sensu; Omurtag, Pinar Sinem; Martens, Steven; Du Prez, Filip E.
Abstract : Several AB′ monomers containing a thiolactone unit and a vinyl ether, separated by a polyethylene oxide (PEO)‐spacer, have been prepared and opened via aminolysis, after which linear poly(amide‐urethane)s with different side chains ( R i ) have been generated by radical polyaddition upon UV irradiation. The obtained polymers have a lower critical solution temperature in water and for specific amines; also, multiresponsive behavior can be obtained. Abstract : AB′ type monomers containing a thiolactone unit and vinyl ether moiety have been prepared with high yields. Aminolysis of the thiolactone moiety generates the corresponding thiol in situ, and upon UV‐irradiation, radical polyaddition occurs in the same medium, yielding linear poly(amide‐urethane)s with different side chain residues and (Poly(Ethylene Oxide)) PEO‐like backbone. Moreover, these unique polymers feature lower critical solution temperature behavior in water. Systematic modification of the responsive polymers reveals the influence of the variation of the side chains and the backbone structure on the corresponding solubility properties. In selected cases, multiresponsive polymers have been developed, which also respond to pH and metal concentration.